(untitled) (Bangladesh Journal of Urology, 2012)
Purpose: To evaluate and compare the effectiveness of 2 different medical therapies during watchful waiting in patients with lower ureteric stones. Materials and Methods: A total of 98 patients with stones less than 1 cm located in the lower ureter (juxtavesical or intramural tract) were enrolled in the study and were randomly divided into 3 groups. Group 1 (33) patients received 1 daily oral therapy of 0.4 mg tamsulosin (maximum 28 days), group 2 (33) received 20 mg nifedipine slow-release (maximum 28 days) and group 3 patients (32) were used as controls. Statistical analyses were performed using Students test, ANOVA test and chi-square test. Results: Of the 98 enrolled patients 91 completed the study. The average stone size for groups 1 to 3 was 5.89, 6.01 and 5.80 mm, respectively, which was not statistically significant. Expulsion was observed in 27 of 32 patients in group 1 (84.38%), 22 of 31 in group 2 (70.97%) and 13 of 28 in group 3 (46.43%). The difference in groups 1 and 2 with respect to group 3 and between groups 1 and 2 was significant. Average expulsion time for groups 1 to 3 was 7.9, 9.3 and 12.8 days, respectively. A statistically significant difference was noted between groups 1 and 3. Mean diclofenac sodium dosage per patient in groups 1 to 3 was 17.5, 24.5, and 100.5 mg, respectively. A statistical significant difference was observed between groups 1 and 2 with respect to group 3. Conclusions: Medical treatments with nifedipine and tamsulosin proved to be safe and effective as demonstrated by the increased stone expulsion rate and reduced need for analgesic therapy. Moreover medical therapy, particularly in regard to tamsulosin, increased expulsion rate reduced expulsion time. BJU 2010; 13(1): 5-9